A Rare Asian Condition - Meadows, Jason (University Clinical, Education & Research Associate (UCERA), 2013)
INTRODUCTION: Hemophagocytic Syndrome (HS) is a rare condition in adults that carries a very poor prognosis. Increased cytokine levels cause excessive activation of T cells and macrophages resulting in the phagocytosis of erythrocytes, leukocytes, and platelets and their precursors. HS in adults can occur secondary to viral illness, autoimmune disease or malignancy. Most malignant causes are T-cell or NK cell lymphoma. B-cell lymhpoma is a rare cause of HS, particularly in Western countries, and has been described almost exclusively in Asia, especially Japan. CASE: An 88-year-old Japanese-American man with chronic iron-deficiency anemia and a history of prostate cancer presented with an approximately 2 month history of progressive fatigue and generalized weakness, associated with dizziness, poor appetite, intermittent nose bleeds and weight loss of 10–15 lbs. He presented to an outside hospital 2.5 weeks prior to admission with several days of chills without fever or night sweats and was discharged after ER workup was unremarkable. Review of systems was otherwise normal. At his primary care appointment 1 week prior to admission he was encouraged to increase oral intake. Basic lab workup at that time was reported to be normal. The patient was noted to be cachectic with pale conjunctivae and a mildly enlarged liver. Lab workup showed significantly elevated LDH, Ferritin, hsCRP as well as pancytopenia. Bone marrow biopsy showed hemophagocytosis. Diagnosis of large B-cell lymphoma with aberrant expression of CD5 and CD13 was made. The patient became progressively dyspneic over the course of his hospitalization. Chest CT scan on hospital day 4 showed mild bilateral lower lobe consolidation and effusion. Despite empiric coverage with broad-spectrum antibiotics, the patient continued to have increasing oxygen requirements and expired on hospital day 5. DISCUSSION: HS is rare, particularly in association with B-cell lymphoma. Our patient met all diagnostic criteria for lymphoma-associated hemophagocytic syndrome including duration of fever >1 week. The presentation and pathologic findings pointed strongly toward this diagnosis. Timely diagnosis of the patient's lymphoma and hemophagocytic syndrome was made but still the patient succumbed to respiratory failure, possibly due to an acute pneumonia or complications of hemophagocytic syndrome. There are no treatment guidelines for hemophagocytic syndrome in adults, although most patients reported in the literature are treated with cytotoxic chemotherapeutic regimens with or without stem cell transplantation. Some case series and case reports have shown significant survival benefit for stem cell transplantation in this setting. CONCLUSIONS: Case reports and case series in the literature are almost exclusively from Japan. This is the first such case reported in Hawaii. While standard treatment is not well established, it likely involves chemotherapeutic agents and either allogeneic or autologous stem cell transplant.